Half-sweep modified successive overrelaxation for solving two-dimensional Helmholtz equations - Md Akhir, Mohd Kamalrulzaman; Othman, Mohamed; Sulaiman, Jumat; Abdul Majid, Zanariah; Suleiman, Mohamed (American-Eurasian Network for Scientific Information, 2011)
The main purpose of this article is to examine the effectiveness of the Half-sweep Modified Successive OverRelaxation (HSMSOR) in solving the sparse linear systems generated form discretization of the two-dimensional Helmholtz equations. In addition, the application and formulation of the HSGS iterative method also presented. Some illustrative examples are given to point out the efficiency of the proposed method.